Transformational leadership strategies: A systematic review - Cesar Del Castillo Oyarse,; Luis Miguel Romero Echevarria,; Denilson Medina Sanchez,; Walter Rolando Zárate Tacca,; Marco Antonio Antón De Los Santos, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Transformational leadership has positioned itself as the most suitable for guiding organizations through the transition processes brought about by the dynamism of the business environment. A systematic review following the PRISMA methodology was carried out for this article, which includes research published in the last five years in Spanish and English. Eighteen articles were selected from Scielo (9) and Scopus (9) out of a total of 31 publications. The literature reviewed highlights the need to opt for this style of leadership, mainly for the digital era, in order to foster innovation and keep the organization relevant and competitive.